The Effect of Roleplay Methods toward Students’ Speaking Skills in Grade XI Senior High School Number 9 Jambi City - Amari, Syarah Sicilia; Wennyta, Wennyta; Yurni, Yurni (Universitas Batanghari Jambi, 2023)
This Study aimed to find out whether or not there was any significant effect of roleplay method toward students’ speaking skills in grade XI Senior High School Number 9 Jambi City. This research used quantitative research method with pre-experimental research design which implicated only experimental class. The total population of this research was the eleventh grade students of Senior High School Number 9 which consisted of 240 students. The samples of this research were chosen by using simple random sampling. The samples were only experimental class consisted of 36 students. The technique of distributing data was speaking test where the students have to choose a topic, make a dialogue and do the role playing with pre-test, treatments, and post-test. This research used t test as the data analysis technique with statistical package for the social sciences (SPSS) for Windows Version 21 Program. The result were found on this research are: (1) Students’ speaking skill taught by normal discussion reached the mean score of 6; (2) students’ speaking skill taught by using role play method reached the mean of 8; (3) students’ speaking skill taught by using role play method is higher than the students’ speaking skill taught by using normal discussion method with a value of sig 0.000 <0.05. Therefore, there are no satisfactory results from this method because the t count is obtained with a value of -4,363.